2018
DOI: 10.1590/s1677-5538.ibju.2017.0524
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes and quality of life after transobturatory slings: hand - made vs. commercial slings

Abstract: Surgical correction is the most efficient treatment for stress urinary incontinence (SUI), and transobturator sling (TO) has optimal results. The high cost of commercially available sling kits makes it difficult the access in most Brazilian public health services. Hand-made polypropylene slings, on the other hand, have been previously reported. The aim of the present study was to compare the effectiveness and safety of commercial vs. hand-made polypropylene mesh slings.Data from 57 women who underwent consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Loss of follow-up in the study (37%) may have been seen as an inherent limitation, but similar rates have been previously reported by Kuprasertkul and Zimmern, who demonstrated rates of loss ranging from 10 to 49% over 10 years follow-up (19). A limited number of publications have studied Safyre™ and all of them used a transobturator approach, with bladder perforation rates varying between 0 -4.2% (1,9,10). Risk factors for bladder injury in this context may include previous pelvic surgeries (cesarean section, colposuspension, rectocele), inexperienced surgeons, local anesthesia, younger patient age and lower body mass index (BMI) (4,20).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Loss of follow-up in the study (37%) may have been seen as an inherent limitation, but similar rates have been previously reported by Kuprasertkul and Zimmern, who demonstrated rates of loss ranging from 10 to 49% over 10 years follow-up (19). A limited number of publications have studied Safyre™ and all of them used a transobturator approach, with bladder perforation rates varying between 0 -4.2% (1,9,10). Risk factors for bladder injury in this context may include previous pelvic surgeries (cesarean section, colposuspension, rectocele), inexperienced surgeons, local anesthesia, younger patient age and lower body mass index (BMI) (4,20).…”
Section: Discussionsupporting
confidence: 70%
“…In a retrospective study comparing transobturator HMS and commercial slings, Ciftci et al reported similar subjective cure rates in both groups after a 12-month follow-up (8) and Lou-renço et al found a comparable rate of subjective cure rates (9). Other authors found subjective cure rates between 59% and 90% (13,15,21).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…1, 2 UVF has also been reported as a rare complication of antiincontinence sling procedures, including tension-free transvaginal tape (TVT) and transobturator tape placement 3 , likely secondary to tension necrosis of the urethra. [4][5][6] Continuous incontinence associated with UVF may mask associated stress urinary incontinence (SUI). Simultaneous surgical correction of incontinence at the time of UVF repair to avoid a secondary surgical intervention is controversial, 7, 8 however small cohort studies have reported concomitant incontinence procedures with success.…”
mentioning
confidence: 99%